2006
DOI: 10.1016/j.bbr.2006.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Feeding, exploratory, anxiety- and depression-related behaviors are not altered in interleukin-6-deficient male mice

Abstract: Interleukin-6 (IL-6) has been implicated in behavioral responses associated with inflammation, sickness behavior and various nervous system disorders. We studied a range of different behaviors in IL-6-knockout (IL-6ko) and wild-type (WT) male mice. No significant differences were observed in ambulatory, exploratory, and stereotypic activities in home or novel cages, in an open field (OF), in the multicompartment chamber (MCC), or in the elevated plus-maze (EPM). IL-6ko mice shed fewer fecal boli than WT mice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 86 publications
1
19
1
Order By: Relevance
“…An inverse correlation between anxiety and depression had already been suggested for rats with low anxiety (Prasad et al, 1997). On the contrary, no significant differences between genotypes were observed in young mice, which in fact is also consistent with a previous study with young total IL-6 KO mice at 6 weeks of age (Swiergiel and Dunn, 2006). Altogether, those results suggest that age is a crucial factor in mediating IL-6 role in depression-like behaviors.…”
Section: Despair Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…An inverse correlation between anxiety and depression had already been suggested for rats with low anxiety (Prasad et al, 1997). On the contrary, no significant differences between genotypes were observed in young mice, which in fact is also consistent with a previous study with young total IL-6 KO mice at 6 weeks of age (Swiergiel and Dunn, 2006). Altogether, those results suggest that age is a crucial factor in mediating IL-6 role in depression-like behaviors.…”
Section: Despair Behaviorsupporting
confidence: 91%
“…Another group confirmed the decrease in rearings and the increase in anxiety using the same IL-6 KO mice, but these authors found opposite results regarding locomotion (Butterweck et al, 2003). Other authors observed altered exploration and anxiety levels of IL-6 KO mice depending on the specific settings (Baier et al, 2009;Butterweck et al, 2003), or genetic background (Swiergiel and Dunn, 2006).…”
Section: Introductionmentioning
confidence: 74%
“…However, the fact that cytokine-induced increased serotonin turnover is dependent on diffuse microglial activation does not favor such a possibility, since there is usually no difference in turnover rates between different brain areas following immune stimulation. 46 The lack of an effect on serotonin turnover does not preclude the possibility of more subtle cytokineinduced alterations in serotoninergic neurotransmission, as might be caused by increases in serotonin transporter expression 47 or modulation of specific serotonin receptor subtype 47 or sensitivity. Studies designed to specifically examine the effects of LPS and IDO activation on the temporal and spatial patterns of 5-HT-related processes in discrete brain regions still need to be carried out before being able to dismiss a possible serotoninergic component in the pathophysiology of LPS-induced depressive-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript describes the simultaneous measurement of numerous metabolic responses to evaluate both energy intake and energy expenditure (food and water intake, locomotor activity, oxygen consumption and respiratory exchange ratio (RER)). Further, we have chosen to examine single cytokine administration (IL-1β and TNF-α, as IL-6 may be less important in mediating immune-associated metabolic changes (Swiergiel and Dunn, 2006), in an effort to determine which metabolic parameters are affected by each cytokine.…”
Section: Introductionmentioning
confidence: 99%